Synthesis and property characterization of two novel side-chain isoindigo copolymers for polymer solar cells - X. Liu; F. Wu; H. Guo; B. Zhao; S. Tan (eXPRESS Polymer Letters)
Two novel side-chain conjugated polymers, PTBT-TID and PTBT-TTID, based on the new synthetic thiophene-benzne-thiophene (TBT) unit, side-chain isoindigo (ID) unit, and the introduced thiophene π-bridge, have been designed and synthesized. The photophysical, electrochemical and photovoltaic properties of the two polymers have been systematically investigated. The two polymers possess relatively good solubility as well as excellent thermal stability up to 380°C, and all of the polymer solar cell (PSC) devices based on the two polymers obtain high open circuit voltage (Voc) of about 0.8 V. The polymer solar cells based on the polymer PTBT-TID show relatively higher efficiencies than the PTBT-TTID-based ones, due to the broader absorption spectrum, a relatively higher hole mobility, a lower HOMO (the highest occupied molecular orbital) energy level, a stronger IPCE (the incident photon to current conversion efficiency) response and a better microphase separation, Consequently, the device based on PTBT-TID:PC61BM (1:2, by weight) gives the best power conversion efficiency (PCE) of 2.04%, with a short-circuit current density (Jsc) of 5.39 mA·cm–2, an open-circuit voltage (Voc) of 0.83 V, and a fill factor (FF) of 0.45.